Selectable multiwavelength thulium-doped fiber laser based on parallel Lyot filter - Jamalus, Muhammad Syauqi Kusyairi; Sulaiman, Abdul Hadi; Abdullah, Fairuz; Zulkifli, Nadiatulhuda; Alresheedi, Mohammed Thamer; Mahdi, Mohd Adzir; Yusoff, Nelidya Md. (Elsevier, 2022)
This paper demonstrates a selectable wavelength spacing of thulium-doped fiber laser (TDFL) based on a parallel Lyot filter. An intensity-dependent loss (IDL) mechanism acts as an amplitude equalizer to flatten and stabilize the multiwavelength spectrum. The IDL mechanism is obtained at a specific polarization state from the combination of highly nonlinear fiber and polarizer. The wavelength spacing of the TDFL can be selected to either 0.9 nm or 1.8 nm when the polarization controllers (PCs) in each branch of the parallel Lyot filter are adjusted. The wavelength spacing is selected by adjusting PC2 and PC3 to suppress or transmit the light at each branch. Up to 4 and 9 lasing lines are generated based on wavelength spacing of 0.9 nm and 1.8 nm, respectively. Lower pump power has disappeared lasing lines, while different half-wave plate angle of PC has shown variation in the laser performances.